2018
DOI: 10.1016/j.apsoil.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Preceding crop and seasonal effects influence fungal, bacterial and nematode diversity in wheat and oilseed rape rhizosphere and soil

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…was reported as the hazardous bacterial population on wheat and Rhizoctonia solani, Mycosphaerella graminicola and Pythium spp. would even cause infections (Hilton et al ., ). Fusarium spp., the common mold on the surface of highland barley, remarkably affects the quality and safety of grains and likely produces mycotoxins, such as deoxynivalenol (DON) and zearalenone, which was considered as a major food safety issue (Legzdina & Buerstmayr, ); (iii) Due to the lack of substantial levels of gluten protein in highland barley flour, proteins do not form a stable network structure (Moza & Gujral, ).…”
Section: Resultsmentioning
confidence: 97%
“…was reported as the hazardous bacterial population on wheat and Rhizoctonia solani, Mycosphaerella graminicola and Pythium spp. would even cause infections (Hilton et al ., ). Fusarium spp., the common mold on the surface of highland barley, remarkably affects the quality and safety of grains and likely produces mycotoxins, such as deoxynivalenol (DON) and zearalenone, which was considered as a major food safety issue (Legzdina & Buerstmayr, ); (iii) Due to the lack of substantial levels of gluten protein in highland barley flour, proteins do not form a stable network structure (Moza & Gujral, ).…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, terminal restriction fragment length polymorphism (TRFLP) can provide as much useful information as high-throughput sequencing at a fraction of the cost and is much more user-friendly for ecological studies (De Vrieze et al 2018) and for use in a commercial laboratory. TRFLP was first tested to identify different bacteria in complex mixtures (Avaniss-Aghajani et al 1994) and has since been found to be highly useful and reliable in determining microbial diversity in many environmental studies, including soil forensics (Habtom et al 2019), soil compaction (Graf et al 2016), crop effects on soil (Hilton et al 2018), postharvest processing (Fröhling et al 2018), and on both modern and ancient corn (Johnston-Monje et al 2016). Molecular fingerprinting of microbial communities in environmental samples have been done using target genes that may be structural (e.g., 16S rRNA gene) or functional (e.g., nifH, encoding dinitrogenase reductase).…”
Section: Introductionmentioning
confidence: 99%
“…18]. For instance, wheat yields benefit from “break crops” such as oilseed rape or other non-host crops to break the life-cycle of wheat-specific pathogens [24]. We focused here on the wheat-oilseed rape rotation, one of the most widely used cropping systems in Europe.…”
Section: Introductionmentioning
confidence: 99%